2022
DOI: 10.1038/s41598-022-06412-3
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer and antimicrobial activity of biosynthesized Red Sea marine algal silver nanoparticles

Abstract: Biosynthesis of silver nanoparticles (AgNPs) is emerging as a simple and eco-friendly alternative to conventional chemical synthesis methods. The role of AgNPs is expanding as antimicrobial and anticancer agents, sensors, nanoelectronic devices, and imaging contrast agents. In this study, biogenic AgNPs were synthesized using extracts of different marine algae species, including Ulva rigida (green alga), Cystoseira myrica (brown alga), and Gracilaria foliifera (red alga), as reducing and capping agents. The Ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(43 citation statements)
references
References 59 publications
3
31
0
Order By: Relevance
“…Compatible with these results, Alsharif et al (2020) reported that chemically and biosynthesized AgNPs exerted an efficient dose-dependent cytotoxic effect against normal Vero cell lines whose viable cell count decreased with increase in AgNPs concentration. Consistent with our study results, incubating human normal cell lines (WI 38) was affected by higher AgNPs concentrations (Salem et al, 2020;Algotiml et al, 2022). Based on the results of the in-vitro cytotoxicity and antibacterial activity, a safe dosage of 100mg/mL was selected for wound patches application to evaluate their antibacterial activity against S1 and E1 strains, the common dermatophyte pathogens found in wounds and burns.…”
Section: Discussionsupporting
confidence: 77%
“…Compatible with these results, Alsharif et al (2020) reported that chemically and biosynthesized AgNPs exerted an efficient dose-dependent cytotoxic effect against normal Vero cell lines whose viable cell count decreased with increase in AgNPs concentration. Consistent with our study results, incubating human normal cell lines (WI 38) was affected by higher AgNPs concentrations (Salem et al, 2020;Algotiml et al, 2022). Based on the results of the in-vitro cytotoxicity and antibacterial activity, a safe dosage of 100mg/mL was selected for wound patches application to evaluate their antibacterial activity against S1 and E1 strains, the common dermatophyte pathogens found in wounds and burns.…”
Section: Discussionsupporting
confidence: 77%
“…Absorption peaks of AgNPs capped by U. rigida , C. myrica , and G. foliifera appearedat 424 nm, 409 nm, and 415 nm, respectively. These types of UV–VIS spectroscopy absorption peak obtained by Algotiml et al 19 . They reported that silver nanoparticles showed a peak value at 422 and 425 nm for Codiumcapitatum seaweeds of dried and fresh respectively.…”
Section: Discussionmentioning
confidence: 88%
“…Thymoquinone (TQ) is one of the most important bioactive elements of black seeds, and it has been found to have numerous health advantages, including cancer prevention and treatment. Following on this, Algotiml et al [250] studied the effect of biosynthesized Red Sea marine algal silver nanoparticles AgNPs on anticancer and antibacterial properties and the authors stated that due to their relatively moderate side effects, marine resources are currently being increasingly examined for antibacterial and anticancer medication prospects.…”
Section: Anticancer Activitymentioning
confidence: 99%